Analysis of Efficiency and Noise, Vibration, and Hardness Characteristics of Inverter for Electric Vehicles According to Pulse Width Modulation Technique - Do-Yun Kim (World Electric Vehicle Journal)
This study investigates the efficiency and noise, vibration, and harshness (NVH) characteristics of electric vehicle (EV) powertrains based on three key Pulse Width Modulation (PWM) techniques: Space Vector PWM (SVPWM), Discontinuous PWM (DPWM), and Random PWM (RPWM). The objective is to evaluate the impact of these PWM techniques on inverter and motor efficiency, as well as their effects on NVH performance, particularly in relation to noise and vibration. Experiments were conducted across various speed and torque levels using a motor dynamo. The study reveals that DPWM provides the highest efficiency, outperforming SVPWM by up to 2.23%. However, DPWM introduces more noise due to increased total harmonic distortion (THD), negatively affecting NVH performance. SVPWM, on the other hand, offers a balanced trade-off between efficiency and NVH, while RPWM demonstrates comparable noise characteristics to SVPWM, with potential for broader harmonic distribution. The findings suggest that each PWM technique offers distinct advantages, and their selection should depend on the required balance between efficiency and NVH.